Cdk5-mediated JIP1 phosphorylation regulates axonal outgrowth through Notch1 inhibition - Im, Doo S.; Joselin, Alvin; Svoboda, Devon; Takano, Tesuya; Rousseaux, Maxime W. C.; Callaghan, Steve; Slack, Ruth S.; Hisanaga, Shin-ichi; Davis, Roger J.; Park, David S.; Qu, Dianbo (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Activated Cdk5 regulates a number of processes during nervous system formation, including neuronal differentiation, growth cone stabilization, and axonal growth. Cdk5 phosphorylates its downstream substrates located in axonal growth cones, where the highly expressed c-Jun N-terminal kinase (JNK)-interacting protein1 (JIP1) has been implicated as another important regulator of axonal growth. In addition, stringent control of the level of intracellular domain of Notch1 (Notch1-IC) plays a regulatory role in axonal outgrowth during neuronal differentiation. However, whether Cdk5-JIP1-Notch1 cooperate to regulate axonal outgrowth, and the mechanism of such joint contribution to this pathway, is presently unknown, and here we explore their potential interaction. Results Our interactome screen identified JIP1 as an interactor of p35, a Cdk5 activator, and we sought to explore the relationship between Cdk5 and JIP1 on the regulation of axonal outgrowth. We demonstrate that JIP1 phosphorylated by Cdk5 at Thr205 enhances axonal outgrowth and a phosphomimic JIP1 rescues the axonal outgrowth defects in JIP1−/− and p35−/− neurons. Axonal outgrowth defects caused by the specific increase of Notch1 in JIP1−/− neurons are rescued by Numb-mediated inhibition of Notch1. Finally, we demonstrate that Cdk5 phosphorylation of JIP1 further amplifies the phosphorylation status of yet another Cdk5 substrate E3-ubiquitin ligase Itch, resulting in increased Notch1 ubiquitination. Conclusions Our findings identify a potentially critical signaling axis involving Cdk5-JIP1-Itch-Notch1, which plays an important role in the regulation of CNS development. Future investigation into the way this pathway integrates with additional pathways regulating axonal growth will further our knowledge of normal central nervous system development and pathological conditions.